Performance evaluation of HVOF sprayed WC-10Co4Cr coatings under slurry erosion. (2nd September 2019) - Liu, Xiao-bin; Kang, Jia-jie; Yue, Wen; Fu, Zhi-qiang; Zhu, Li-na; She, Ding-shun; Liang, Jian; Wang, Cheng-biao
ABSTRACT: Slurry erosion is one of the main failure modes of the hydraulic turbine parts, mud pumps and drill pipes. The high velocity oxygen fuel (HVOF) spray process has been widely used for depositing protective coatings especially the cermet coatings that can significantly improve the slurry erosion resistance of substrate materials. In this work, conventional WC-10Co4Cr composite coatings and coatings with bimodal structures were deposited on the 35CrMo steel substrate by HVOF, respectively. Structures of the two kinds of coatings were analysed with SEM and XRD methods, and microhardness, porosity and roughness were also measured. Furthermore, the slurry erosion tests were carried out on the coatings to explore the effect of average particle size, slurry concentration and pH value on the erosion behaviours. The erosion failure mechanisms of the coatings were also explored. The results show that the bimodal coating has a denser microstructure, superior mechanical properties, lower porosity and better slurry erosion resistance than the conventional coating. The erosion-corrosion mechanism of the two kinds of coatings is spalling, caused by crack initiation and propagation under fatigue stress.